Inspiratory muscle training improves thoracic expansion and six-minute walking distance in female subjects with inspiratory muscle weakness - Boonla, Orachorn; Prasertsri, Piyapong; Srithawong, Arunrat (Journal of Physiological and Biomedical Sciences, 2020)
During physical activity, ventilation is elevated due to an increase in both the depth and frequency of breathing. The increase in breathing depth during training is attained by greater contraction of the diaphragm, external intercostal muscle, and accessory muscles. Fatigue of the respiratory muscles is an exercise-limiting factor by reducing exercise performance in healthy subjects. Maximum inspiratory pressure (MIP) serves as an indicator of inspiratory muscle strength. It seems that inspiratory muscle training (IMT) increases the strength of the inspiratory muscles, chest expansion, functional capacity and exercise performance. However, effects of IMT on chest expansion and functional capacity in subjects with inspiratory muscle weakness are not well defined. Therefore, the objective of this study was to evaluate whether IMT could improve chest expansion, diaphragmatic movement, and functional capacity in subjects with inspiratory muscle weakness. Eight female subjects displaying respiratory muscle weakness with less than 80% predicted MIP were recruited in this experiment. All subjects were assessed for their MIP, thoracic expansion (upper and lower thoracic expansion), diaphragmatic movement, and a six-minute walking distance procedure (6MWD) at pre- and post-training intervals. The respiratory IMT program was performed using a Threshold Inspiratory Muscle Trainer at 80% MIP over 10 repetitions/set, 3 sets/day, 5 days/week, throughout 8 weeks. Results suggested that IMT at 80% of MIP for 8 weeks improved the strength of the inspiratory muscles in subjects with respiratory weakness, as shown by significantly raising MIPs compared with pre-training results. It also appeared that subjects with IMT exhibited increased lower thoracic expansion and diaphragmatic movement when compared with pre-training results. 6MWD outcomes also improved in subjects with inspiratory muscle weakness. Therefore inspiratory muscle training improves the strength of the inspiratory muscles, thoracic expansion, diaphragmatic movement, and 6MWD in trained subjects with inspiratory muscle weakness.